Psychometric Properties of the Persian Version of Adult Eating Behavior Questionnaire in Patients with Epilepsy - Abbas Shamsalinia; Reza Ghadimi; Reza Ebrahimi Rad; Khadije Jahangasht Ghoozlu; Amaneh Mahmoudian; Mozhgan Moradi; Reza Masoudi; Fatemeh Ghaffari (Iranian Journal of Medical Sciences, 2022)
Background: Adult eating behavior questionnaire (AEBQ) is an age upward extension tool that measures appetite traits in individuals. This instrument was developed by Hunot in 2016. The present study aimed to determine the psychometric properties of the Persian version of AEBQ in adults with epilepsy.Methods: The current research is a cross-sectional study conducted in 2019 in Iran. 700 adults with epilepsy completed the 35-item AEBQ. Qualitative face validity, qualitative content and structure validity (exploratory factor analysis [EFA], N=400, and confirmatory factor analysis [CFA], N=300) appetitive traits were evaluated. Reliability was also measured using Cronbach’s alpha, Construct reliability (CR), and Intra-Class Correlation (ICC). The SPSS 26-AMOS24 software was employed to analyze the data with a significance level of 0.05. Results: The EFA and CFA results comprised eight factors, namely enjoyment of food, emotional over-eating, food responsiveness, hunger, satiety responsiveness, emotional under-eating, food fussiness, and eating slowly. Indices of root mean square error of approximation=0.068, parsimonious normed fit index=0.644, parsimonious comparative fit index=0.671, adjusted goodness of fit index=0.618, goodness of fit index=0.911, and Chi square degree-of-freedom ratio (normalized Chi square CMIN/DF=2.842) confirmed the fitness of the final model. Convergent and divergent validity was acceptable for all the factors. The results revealed that the internal stability>0.8 and CR>0.7 of the eight extracted AEBQ structures are confirmed. The ICC was 0.899 (95% CI: 0.878-0.917; P<0.001). The results also showed that AEBQ has acceptable convergent and divergent validity.Conclusion: The eight-factor structure of AEBQ can measure eating behavior traits and is of good validity and reliability for assessing the eating behavior of Iranian adults with epilepsy.